Maternal smoking as an independent risk factor for the development of severe retinopathy of prematurity in very preterm infants - Hudalla, Hannes; Bruckner, Thomas; Pöschl, Johannes; Strowitzki, Thomas; Kuon, Ruben-Jeremias (Eye, 2021)
Retinopathy of prematurity (ROP) is a severe neonatal complication potentially leading to visual impairment and blindness. Known risk factors include preterm birth, low birth weight and respiratory support. Limited and contradictory data exist on the risk of maternal smoking during pregnancy on the development of ROP. This study aims to investigate smoking as an independent risk factor for the development of severe ROP (≥stage 3).